Construct the filter for malware detection in distributed control system. Issue 5 (4th July 2019) - Yask,; Kumar, B. Suresh
Abstract: This paper explores the basic design of control system and the malfunctioning of the process. This paper is the small attempt to simulate the control system through MATLAB and try to generate the malfunction. Further a detection filter is used to get the malware activities in Distributed control systems. The MALTAB Simulink is used to construct the distributed control system using the network dynamics, gain circuitry, intruder detection, Filter etc.